The Effect Of Load, Stress And Job Satisfaction On The Performance Of Health Workers In The Nursing Home Unit - Dharma Jaya Hartono; Kosasih; Ayu Laili Rahmiyati; Farida Yuliatya; Vip Paramarta (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Low performance of healthcare workers can reduce the quality of hospital services. The aim of this study is to provide an overview about effect of workload, work stress, and job satisfaction to healthcare workers, and how these factors affect their performance, particularly among nurses and midwives in the inpatient unit of Palmatak Regional Public Hospital (RSUD Palmatak), Anambas Islands, Riau Islands. This is a quantitative study using a cross-sectional data collection approach conducted from June to July 2025. The study sample consisted of 30 respondents with independent variables were workload, work stress, and job satisfaction, while the dependent variable was the performance of healthcare workers. The data were analyzed using univariate, bivariate (Chi-Square), and multivariate (Logistic Regression) analyses.The results showed that In the inpatient ward of RSUD Palmatak, low workload was reported in 66.7% of respondents, low job stress in 73.3%, high job satisfaction in 76.6%, and good performance in 70%. Bivariate analysis revealed a significant influence of workload, job stress, and job satisfaction on healthcare worker performance (p < 0.05). Multivariate analysis indicated that job satisfaction was the most influential factor affecting healthcare worker performance.